2009
DOI: 10.1007/s00415-009-5120-8
|View full text |Cite
|
Sign up to set email alerts
|

Ocular myasthenia gravis: treatment successes and failures in patients with long-term follow-up

Abstract: We previously reported that prednisone reduced the frequency of generalized myasthenia (GMG) and controlled diplopia without major adverse effects at 2 years in patients with ocular myasthenia gravis (OMG). Questions remain as to whether study subjects had long-standing disease, biasing results towards a steroid benefit, and if prednisone merely delayed GMG onset. Here, we performed a record review of a referral neuro-ophthalmology service OMG database for patients who were followed-up for > or =4 years or unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 24 publications
3
64
2
2
Order By: Relevance
“…To enable a better comparison of our findings with the previous results we compiled the generalization risks with or without early corticosteroid treatment observed in the previously published studies (Table 3). This crude comparison shows that, except for one small study [11], all other investigations find the generalization risks under corticosteroids to be below 17%, but without immunosuppressive treatment this risk increases to between 26% and 86%, corresponding to risk ratios of 0.14-0.32 [4,9,10,[12][13][14][15][16]]. An interesting question in this context is whether corticosteroids would reduce the risk of generalization only for the duration of the treatment or whether this possible protective effect could last on, even if the medication itself is discontinued or at least much reduced.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To enable a better comparison of our findings with the previous results we compiled the generalization risks with or without early corticosteroid treatment observed in the previously published studies (Table 3). This crude comparison shows that, except for one small study [11], all other investigations find the generalization risks under corticosteroids to be below 17%, but without immunosuppressive treatment this risk increases to between 26% and 86%, corresponding to risk ratios of 0.14-0.32 [4,9,10,[12][13][14][15][16]]. An interesting question in this context is whether corticosteroids would reduce the risk of generalization only for the duration of the treatment or whether this possible protective effect could last on, even if the medication itself is discontinued or at least much reduced.…”
Section: Discussionmentioning
confidence: 94%
“…Six of the available seven small retrospective studies have identified a reduced generalization rate under steroids when assessed within the first 2 years of treatment with relative risks in the range from 0.14 to 0.32, whereas the seventh study observed an increased risk with corticosteroids [4,[9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 95%
“…Although the ability of corticosteroids and azathioprine to prevent secondary generalization of OMG is uncertain, 22 several authors have reported a favorable outcome in individuals with OMG treated early with immunotherapy. 12,[23][24][25][26][27] Among individuals with OMG treated with corticosteroids, symptoms of generalized MG were reported in 7% and 11% of patients within 2 years. 23,24 In a study of 120 patients treated with immunotherapy after the age of 60, most with GMG, good therapeutic results (defined as remission, pharmacologic remission, or marked improvement) were recorded in 76% of those treated with prednisone and 89% of those treated with both prednisone and azathioprine.…”
Section: Discussionmentioning
confidence: 99%
“…With an overall prevalence of 12 cases per 100000, ocular MG (OMG) shares the very same process with MG and affects almost half of MG patients, but its symptoms are restricted to the extraocular and levator palpebrae muscles, which take the form of diplopia and ptosis [2]. OMG can lead to visual disabilities and disrupt daily activities, and approximately 44% OMG patients are reported to develop generalized MG, which even poses a threat to survival [3]. Therefore, early diagnosis and treatment are fundamentally important.…”
Section: Introductionmentioning
confidence: 99%